High-voltage-resistant thick electrode, preparation method and battery cell

By coating the active material with halide electrolyte in situ and mixing it with other materials, a high-voltage-resistant thick electrode is formed, which solves the problem of unstable all-solid-state batteries under high voltage and significantly improves the battery's high-voltage-resistant stability sex.

CN119480926AInactive Publication Date: 2025-02-18CRINM (GUANGDONG) INST FOR ADVANCED MATERIALS & TECH
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411634089.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing all-solid-state batteries are unstable at high voltages, resulting in interface side reactor accumulation and affecting battery performance.

Method used

By coating the active material in situ with the first halide electrolyte material and mixing it with the second halide solid electrolyte, conductive carbon and polymer adhesive, a high-voltage thick electrode is formed.

Benefits of technology

It improves the high voltage resistance of the electrode, ensures stability under high voltage, reduces interface side reactions, and significantly improves the high voltage resistance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480926A_ABST
    Figure CN119480926A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a thick electrode. The preparation method comprises the following steps: S1, effectively coating a first halide electrolyte material coated active substance material with a first halide electrolyte material to obtain active substance preparation; the active substance material is one or more of LiCoO2, Li2MnO4, LiFePO4 and LiNi < 1-x-y > Co < x > Mn < y > O2, and 0 < lt >; xlt; 0, 0.5, 0 lt; yt; Yt; 0.5 part; and S2, sequentially mixing the active substance preparation body obtained in the step S1 with a second halide solid electrolyte, conductive carbon and a high-molecular polymer adhesive for three times, thinning, and carrying out double-sided compounding with a current collector to obtain the thick electrode. The high-voltage resistance of the electrode can be improved, the electrode can be kept stable under high voltage, and the interface cannot generate side reaction, so that the interface transmission of the positive electrode material cannot be hindered. The thickness of the obtained thick electrode can reach 100-300 microns.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solid-state batteries, and in particular to a high-voltage resistant thick electrode, a preparation method thereof, and a battery cell. Background Art

[0002] In recent years, with the continuous development of the new energy battery industry, lithium-ion batteries have made great progress. Their energy density and the capacity of single cells have also been continuously improved in recent years. However, in terms of the current battery industry, the traditional liquid battery system is mature, but it is difficult to achieve a significant performance breakthrough. From the perspective of both high energy density and intrinsic safety, all-solid-state lithium-ion batteries with solid electrolytes will become the battery with the most technologically disruptive potential in the future. Their energy density can easily break through the extreme value of current liquid batteries. Not only that, since solid-state batteries use all-solid-state electrolytes that do not contain electrolytes, they can have excellent safety performance. For solid-state batteries, the core of their high energy density lies in the electrodes doped with solid electrolytes. Under the current technological status, the thinning thickness of the current collector is already close to the process limit. Although the current all-solid-state battery positive electrode material can improve the high voltage resistance of the electrode, it is not stable under high voltage conditions. The side reaction accumulation that may occur at the interface hinders the interface transmission of the positive electrode material and affects the performance of the battery. Summary of the invention

[0003] To solve the above problems, the present invention aims to provide a high-voltage resistant thick electrode and a preparation method and a battery cell. The preparation method can improve the high-voltage resistance of the thick electrode, and can remain stable under high voltage, reduce interface side reactions, and significantly improve the high-voltage resistance stability, solving the technical problem of high-voltage resistance of solid-state batteries under thick electrodes. A thick electrode and a battery cell are also provided.

[0004] The present invention is achieved through the following technical solutions:

[0005] A method for preparing a high-voltage resistant thick electrode comprises the following steps: S1, coating an active material with a first halide electrolyte material for in-situ coating to obtain an active material preparation, wherein the first halide electrolyte material is Li a MX4, Li a MX6, Li a One or more of MX8, M is a metal element, X is a halogen element, the Li element mainly comes from one or more of Li oxides, carbonates, chlorides, and hydroxides, and the value of a ranges from 1 to 3; the active material is LiCoO2, Li2MnO4, LiFePO4, LiNi 1-x-y Co x Mn yOne or more of O2, where 0 < x < 0.5 and 0 < y < 0.5; S2. First, the active material precursor obtained in S1 is mixed with a second halide solid electrolyte to obtain a secondary active material precursor. Then, the secondary active material precursor is mixed with conductive carbon for a second time, and after adding a polymer binder and undergoing a third mixing and thinning, it is double-sidedly laminated with a current collector to obtain a thick electrode. The second halide solid electrolyte is Li a MX4, Li a MX6, Li a One or more of MX8, where M is a metal element and X is a halogen element. The Li element mainly comes from one or more of oxides, carbonates, chlorides, and hydroxides of Li. The value range of a is 1 - 3.

[0006] During implementation, the coating layer thickness of the first halide electrolyte is 10 - 50 nm. During implementation, optional coating methods include one or more of high - low speed uniform three - dimensional mixing, medium - small particle size ball stone mixing and stirring grinding method, ultrafine pulverization high - speed air impact method, and precise temperature - controlled ball milling method. In the present invention, by effectively in - situ coating the active material, and then doping and mixing the in - situ coated active material with the second halide solid electrolyte through a powerful mixer to improve the high - voltage resistance of the electrode material, the high - voltage resistance of the electrode is improved, and it can remain stable under high voltage. Therefore, the main idea of the present invention is: compared with some existing so - called coatings that actually modify the halide electrolyte, by effectively in - situ coating the positive electrode material applied to the solid - state battery with halide, the problem of instability of the solid - state battery with a thick electrode under high voltage is solved. In the present invention, the mixing process with the second halide solid electrolyte, conductive carbon, polymer binder, etc. is not a coating process.

[0007] During implementation, the first halide electrolyte material and the second halide solid electrolyte material can be the same, and Li3InCl6, LiAlF4, Li3YCl6, etc. can be selected, that is, trivalent metal cations are selected. The reason for selecting the halide electrolyte material in this valence state in the present invention is that when a = 3, this type of material has the highest room - temperature lithium - ion conductivity (>2.7×10 -3 S·cm -1 ), and when a is less than 3, the lithium - ion conductivity of the electrolyte will decrease, and the level of its ionic conductivity will directly affect the high - voltage stability of the electrode material and the capacity retention rate of the all - solid - state battery.

[0008] The conductive carbon is one or more of microporous carbon (pore diameter less than 2 nm), mesoporous carbon (pore diameter between 2 and 50 nm), and macroporous carbon (pore diameter greater than 50 nm).

[0009] The mass ratio of active material preparation, second halide solid electrolyte, conductive carbon and high molecular polymer binder is 96-98:0.5-1.5:1:0.5-1.5. This ratio ensures the proportion of high active material while strictly controlling the amount of polymer binder added, and does not reduce the conductivity while ensuring effective cross-linking effect with each component material.

[0010] The temperature of the active material preparation and the second halide solid electrolyte mixture in S2 is controlled at 45°C to 50°C. In practice, the temperature generally rises gradually during the mixing process. The inventors have found that a good mixing effect can be achieved within the range of 45°C to 50°C, and the air inside the mixing tank will not be overheated due to excessive temperature, resulting in serious spraying, wall sticking, etc.

[0011] During the second mixing process with the conductive carbon, the temperature is controlled at 16-17°C.

[0012] Before double-sided compounding with the current collector, the mixture after three mixings needs to be thinned to 50um to 150um. The thinning method is mechanical means, such as one or more of electrostatic spraying, hot pressing compounding, and vapor deposition. The thickness of the current collector is 10 to 20um.

[0013] A high-voltage thick electrode is obtained by first mixing an active material preparatory body effectively coated with a first halide electrolyte material with a second halide solid electrolyte to obtain an active material secondary preparatory body, then mixing the active material secondary preparatory body with conductive carbon for a second time, adding a high molecular polymer adhesive for a third time mixing and thinning, and then double-sided compounding with a current collector to obtain the electrode, wherein the first halide electrolyte material and the second halide solid electrolyte material are both Li a MX4, Li a MX6, Li a One or more of MX8, M is a metal element, X is a halogen element, the Li element mainly comes from one or more of Li oxides, carbonates, chlorides, and hydroxides, a ranges from 1 to 3, and the active material is LiCoO2, Li2MnO4, LiFePO4, LiNi 1-x-y Co x Mn y One or more of O2, 0 <x<0.5,0<y<0.5。

[0014] The thickness of the high voltage resistant thick electrode is 100um to 300um.

[0015] A battery cell comprises the high-voltage resistant thick electrode as described above.

[0016] The above-mentioned battery cell is composed of a high-voltage thick electrode, a third halide solid electrolyte membrane, and a negative electrode plate. The third halide solid electrolyte is Lia MX4, Li a MX6, Li a One or more of MX8, M is a metal element, X is a halogen element, the Li element mainly comes from one or more of Li oxides, carbonates, chlorides and hydroxides, and a ranges from 1 to 3.

[0017] The negative electrode plate can be a graphite plate, and the graphite plate is one or more of natural graphite, artificial graphite, composite graphite, and mesophase carbon microspheres.

[0018] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0019] The invention can improve the high voltage resistance of the electrode, and can maintain stability under high voltage, and no side reaction will occur at the interface, thereby not hindering the interface transmission of the positive electrode material. The thick electrode obtained by the invention can reach 100-300 microns. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:

[0021] Figure 1 Schematic diagram of the preparation process of Example 1 of the present invention DETAILED DESCRIPTION

[0022] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0023] Example 1

[0024] Step 1:

[0025] 970 g of NCM523 (LiNi 0.5 Co 0.2 Mn 0.3 O2), 15g of Li3InCl6 solid electrolyte are uniformly mixed at high speed (600rpm~2500rpm) by a strong mixer until the material temperature reaches 40℃~45℃, and the coated active material is fully mixed with the halide solid electrolyte;

[0026] Step 2:

[0027] 10 g of conductive carbon (2-50 nm) was put into a strong mixer for a second uniform high-speed mixing (700 rpm-2000 rpm), while the material temperature was controlled at 16°C-17°C;

[0028] Step 3:

[0029] 15 g of PTFE was added to the strong mixer for a third uniform high-speed mixing (900 rpm to 3000 rpm). When the material temperature reached 80°C, the material was discharged to obtain a mixture with obvious fibrosis.

[0030] Step 4:

[0031] The fiberized mixed material is repeatedly rolled by a hot roller at 100°C, and the rolling thickness is continuously adjusted (2000um to 100um), so that the fibrous material is gradually pressed into a composite layer of 50um to 150um;

[0032] Step 5:

[0033] The hot-pressed composite layer is double-sidedly composited with the current collector to obtain a thick electrode with a thickness of 100um to 300um;

[0034] Step 6:

[0035] 50g of Li3InCl6 solid electrolyte was gradually thinned from 2500um to a film with a thickness of 120um to 240um by a hot roller machine (60℃);

[0036] Step 7:

[0037] The already composited thick electrode, Li3InCl6 solid electrolyte membrane and graphite pole piece are cut into 60mm×80mm rectangles, stacked in sequence and packaged to obtain an all-solid-state battery.

[0038] Embodiment 2:

[0039] Step 1:

[0040] 970 g of NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2), 10g of LiAlF4 solid electrolyte are uniformly mixed at high speed (600rpm~2500rpm) by a strong mixer until the material temperature reaches 40℃~45℃, and the coated active material is fully mixed with the halide solid electrolyte;

[0041] Step 2:

[0042] 10 g of conductive carbon (>50 nm) was put into a strong mixer for a second uniform high-speed mixing (700 rpm to 2000 rpm), while the material temperature was controlled at 16° C. to 17° C.;

[0043] Step 3:

[0044] 10 g of PTFE was added to the strong mixer for a third uniform high-speed mixing (900 rpm to 3000 rpm). When the material temperature reached 80°C, the material was discharged to obtain a mixed material with obvious fibrosis.

[0045] Step 4:

[0046] The fiberized mixed material is repeatedly rolled by a hot roller at 100°C, and the rolling thickness is continuously adjusted (2000um to 100um), so that the fibrous material is gradually pressed into a composite layer of 50um to 150um;

[0047] Step 5:

[0048] The hot-pressed composite layer is double-sidedly composited with the current collector to obtain a thick electrode with a thickness of 100um to 300um;

[0049] Step 6:

[0050] 50g of LiAlF4 solid electrolyte was gradually thinned from 2500um to a film with a thickness of 120um to 240um by a hot roller machine (60°C);

[0051] Step 7:

[0052] The already composited thick electrode, LiAlF4 solid electrolyte membrane, and graphite pole piece are cut into 60mm×80mm rectangles, stacked in sequence, and packaged to obtain an all-solid-state battery. Figure 1 shown.

[0053] Example 3

[0054] Step 1:

[0055] 980 g of NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2), 5g of Li3YCl6 solid electrolyte are uniformly mixed at high speed (600rpm~2500rpm) by a strong mixer until the material temperature reaches 40℃~45℃, so that the active material is fully coated in the halide solid electrolyte;

[0056] Step 2:

[0057] 10g of conductive carbon (>50nm) was put into a strong mixer for a second uniform high-speed mixing (700rpm-2000rpm), while the material temperature was controlled at 16°C-17°C;

[0058] Step 3:

[0059] 5g of PTFE was added to a strong mixer for a third uniform high-speed mixing (900rpm-3000rpm). When the material temperature reached 80°C, the material was discharged to obtain a mixed material with obvious fibrosis. During the implementation, the temperature of other mixed materials was controlled to about 50°C before PTFE was added. After the addition of PTFE, the high-speed mixing would instantly increase the temperature. When it reached 55°C, PTFE began to show its excellent adhesion and cross-linking effect, thereby avoiding the negative impact of the irreversible phase change that occurred when the temperature was slowly increased to 19°C on the subsequent reaction.

[0060] Step 4:

[0061] The fiberized mixed material is repeatedly rolled by a hot roller at 100°C, and the rolling thickness is continuously adjusted (2000um to 100um), so that the fibrous material is gradually pressed into a composite layer of 50um to 150um;

[0062] Step 5:

[0063] The hot-pressed composite layer is double-sidedly composited with the current collector to obtain a thick electrode with a thickness of 100um to 300um;

[0064] Step 6:

[0065] 50g Li3YCl6 solid electrolyte was gradually thinned from 2500um to a film with a thickness of 120um to 240um by a hot roller machine (60°C).

[0066] Step 7:

[0067] The already composited thick electrode, Li3YCl6 solid electrolyte membrane and graphite pole piece are cut into 60mm×80mm rectangles, stacked in sequence and packaged to obtain an all-solid-state battery.

[0068] Comparative Example 1

[0069] This comparative example provides a method for manufacturing a thick electrode and an all-solid-state battery cell. The active material NCM523 (LiNi 0.6 Co 0.2 Mn 0.2 O2) No coating method is used, and the remaining materials and subsequent process are the same as those in Example 1.

[0070] Comparative Example 2

[0071] This comparative example provides a method for manufacturing a thick electrode and an all-solid-state battery cell. The active material NCM523 (LiNi 0.6 Co0.2 Mn 0.2 O2) is in-situ coated with lithium phosphate, and the remaining materials and subsequent process are the same as those in Example 1.

[0072] Comparative Example 3

[0073] This comparative example provides a method for manufacturing a thick electrode and an all-solid-state battery cell. The active material NCM523 (LiNi 0.6 Co 0.2 Mn 0.2 O2) is coated with Al2O3 and Li3YCl6 double materials, and the remaining materials and subsequent process are the same as those in Example 1.

[0074] The thick electrodes described in the above embodiments and comparative examples were assembled into an all-solid-state battery, and the capacity retention rate was tested at different cut-off voltages under 0.3C conditions. The test data are shown in Tables 1 and 2:

[0075] Table 1

[0076] Group Cut-off voltage(V) Cycle times Capacity retention rate (%) Example 1 4.3 100 84.02 Example 2 4.3 100 82.79 Example 3 4.3 100 83.43 Comparative Example 1 4.3 100 62.06 Comparative Example 2 4.3 100 73.51 Comparative Example 3 4.3 100 59.63

[0077] Table 2

[0078] Group Cut-off voltage(V) Cycle times Capacity retention rate (%) Example 1 4.5 100 83.15 Example 2 4.5 100 81.53 Example 3 4.5 100 82.01 Comparative Example 1 4.5 100 60.71 Comparative Example 2 4.5 100 70.16 Comparative Example 3 4.5 100 50.32

[0079] The test data shows that the capacity retention rate under different cut-off voltages is high under high pressure, proving that the present invention has good high-voltage stability. It can be seen that the present invention uses an active material material coated in situ with a halide electrolyte, and then mixes with a second halide electrolyte material and the like through temperature control and thinning to form a thick electrode. In terms of being used in all-solid-state batteries, compared with an all-solid-state battery composed of an uncoated active material material, a lithium phosphate-coated, and an Al2O3 and halide double-coated active material material, its capacity retention rate has been significantly improved, intuitively reflecting the excellent high-voltage stability.

[0080] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a high voltage resistant thick electrode, characterized in that: The following steps are involved: S1. Coating the active material with the first halide electrolyte material for in-situ coating to obtain a precursor of the active material. The first halide electrolyte material is one or more of Li a MX4, Li a MX6, Li a MX8, where M is a metal element and X is a halogen element. The Li element is derived from one or more of Li oxides, carbonates, chlorides, and hydroxides, and the value range of a is 1 - 3. The active material is one or more of LiCoO2, Li2MnO4, LiFePO4, LiNi 1-x-y Co x Mn y O2, where 0 < x < 0.5 and 0 < y < 0.

5. S2. First, mixing the precursor of the active material obtained in S1 with the second halide solid electrolyte to obtain a secondary precursor of the active material. Then, after mixing the secondary precursor of the active material with conductive carbon, adding a polymer binder, mixing for the third time, thinning, and then double-sidedly laminating with a current collector to obtain a thick electrode. The second halide solid electrolyte is one or more of Li a MX4, Li a MX6, Li a MX8, where M is a metal element and X is a halogen element. The Li element is derived from one or more of Li oxides, carbonates, chlorides, and hydroxides, and the value range of a is 1 - 3.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the active material preparation, the second halide solid electrolyte, the conductive carbon and the high molecular polymer binder is 96-98:0.5-1.5:1:0.5-1.

5.

3. The preparation method according to claim 1, characterized in that: The conductive carbon is one or more of microporous carbon, mesoporous carbon and macroporous carbon.

4. The preparation method according to claim 1, characterized in that: The temperature of the active material preparation and the second halide solid electrolyte mixture in S2 is controlled at 45°C to 50°C.

5. The preparation method according to claim 1, characterized in that: During the second mixing process with the conductive carbon, the temperature is controlled at 16-17°C.

6. The preparation method according to claim 1, characterized in that: Before double-sided compounding with the current collector, the mixture after three mixings needs to be thinned to 50um to 150um to make a high-voltage resistant thick electrode.

7. A high voltage resistant thick electrode as claimed in any one of claims 1 to 6, characterized in that: The active material preparatory body effectively in-situ coated by the first halide electrolyte material is first mixed with the second halide solid electrolyte to obtain the active material secondary preparatory body, and then the active material secondary preparatory body is mixed with the conductive carbon for a second time, and then a high molecular polymer adhesive is added to mix and thin for a third time, and then double-sided composite with the current collector is obtained, and the first halide electrolyte material and the second halide solid electrolyte material are both Li a MX4, Li a MX6, Li a One or more of MX8, M is a metal element, X is a halogen element, the Li element is derived from one or more of Li oxides, carbonates, chlorides, and hydroxides, a is in the range of 1-3, and the active material is LiCoO2, Li2MnO4, LiFePO4, LiNi 1-x-y Co x Mn y One or more of O2, 0 <x<0.5,0<y<0.5。 8. The high voltage resistant thick electrode according to claim 7, characterized in that: The thickness of the high voltage resistant thick electrode is 100um to 300um.

9. A battery cell, characterized in that: Comprising the high voltage resistant thick electrode as described in claim 7 or 8.

10. The battery cell according to claim 9, characterized in that: It is composed of a high-voltage thick electrode, a third halide solid electrolyte membrane, and a negative electrode. The third halide solid electrolyte is Li a MX4, Li a MX6, Li a One or more of MX8, M is a metal element, X is a halogen element, the Li element is derived from one or more of Li oxides, carbonates, chlorides, and hydroxides, and a is in the range of 1-3.

Citation Information

Patent Citations

  • Lithium-rich manganese-based solid-state battery electrode and secondary battery

    CN111129429A

  • Positive electrode material layer for all-solid-state battery, preparation method of positive electrode material layer, positive electrode sheet and all-solid-state battery

    CN112151744A

  • Positive pole piece for solid-state battery, preparation method and application thereof

    CN113921767A

  • High-voltage positive electrode material coated with inorganic solid electrolyte as well as preparation method and application of high-voltage positive electrode material

    CN114824247A

  • Dry-method battery material mixing method and dry electrode diaphragm preparation method

    CN116031360A